Evaluating Key Biomotor Abilities: A Comparison between National and International Elite Tennis Players - Pratham Singh; Dharmander Kumar; Mohit Morya; Rishabh Singh; Md. Hamidur Rahman (OVS LLC, 2024)
Background. Biomotor ability is essential for elite tennis players, as it significantly contributes to increased efficiency, responsiveness and overall performance on the court. Objectives. This study aimed to assess and measure the biomotor abilities of elite tennis players, examining both national and international levels, and focusing on their physical and motor performance. Materials and methods. The research involved a cross-sectional study of a total of 28 tennis players; among them, 15 were national players, and the remaining 13 were international players who served as subjects. The study focused on assessing eight key biomotor abilities: arm-shoulder strength and endurance, static muscular endurance, grip strength, power, speed, agility, and flexibility. Each test was conducted using appropriate equipment and standardized procedures, ensuring accurate score recording for analysis. The data was gathered at Super Shots Tennis Academy and Punjabi Bagh Club in Delhi, India. The statistical analysis involved calculating descriptive statistics (mean and standard deviation) and conducting an independent t-test to determine significance. The analysis was performed using SPSS Version 25, with a significance level of 0.05. Results. The independent t-test comparing the biomotor abilities of international and national tennis players showed no significant differences in pull-ups, push-ups, speed, agility, or flexibility (p > 0.05). However, significant differences were found in wall squat hang, vertical jump, and hand grip strength (p < 0.01), with international players demonstrating superior performance. Conclusions. In conclusion, the study reveals notable differences in certain biomotor abilities between international and national players, especially in static muscular endurance, explosive leg power, and hand grip strength. The findings suggest that national tennis players implementing targeted strength and power exercises, along with specialized endurance training, may exhibit enhanced overall biomotor abilities and improved on-court performance.